PERSPEKTIF MAHASISWA PGSD TERHADAP MATAKULIAH ADAT MELAYU DALAM MELESTARIKAN BUDAYA MELAYU JAMBI - Destrinelli, Destrinelli; Alirmansyah, Alirmansyah; Handayani, Kiki; Darmawan, Aldo; Hajar, Khaini; Dewangga, Fadjar; Unai, Dina Hermina (JURNAL ILMU BUDAYA, 2020)
This research was conducted to describe the perspective of PGSD students towards Malay traditional subjects in preserving the Malay Malay culture of Jambi. This research was conducted in October to December 2019. This research was a descriptive qualitative study. The subjects in this study were PGSD University of Jambi students, data collection in this study using observation, interviews, and documentation. The results of a study of PGSD Jambi University students showed that in the Jambi Malay customary course, students fully supported the Malay customary course program in preserving the Malay culture in Jambi. But there are still many shortcomings in preserving this matter, namely from the lack of facilities and infrastructures that are still inadequate and also the schedule of other solid courses so as to give a time limit for students in preserving Jambi culture.